2022
DOI: 10.18280/ijsdp.170135
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Knowledge and Policy Sustainability: A Study of Pro Environmental Policy Support among the Southeast Nigerian Rural Communities

Abstract: Environmental policy sustainability as part of the Sustainable Development Goals (SDGs) agenda has appeared as one of the challenges to most developing nations such as Nigeria. This inadvertently has affected (SDG) agenda in Nigeria. Although many scholars have given attention to other dimensions of socio-economic policies/natural environment, the case of environmental policy sustainability has received virtually no attention in some regions such as southeast Nigeria. The study aptly captured the context of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Environmental knowledge and policy sustainability are also crucial for achieving the SDGs in Nigeria (Okafor et al, 2022). Environmental sustainability is one of the challenges faced by developing nations like Nigeria.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…Environmental knowledge and policy sustainability are also crucial for achieving the SDGs in Nigeria (Okafor et al, 2022). Environmental sustainability is one of the challenges faced by developing nations like Nigeria.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…Mangrove rehabilitation has been carried out on the initiative of the local community since 1984 [8]. The local community's environmental knowledge and attitudes toward mangrove protection and sustainable management are thought to be the trigger [10,11]. Sugandini et al [12] revealed that environmental knowledge and perceived environmental responsibility influence attitudes and decisions to protect mangroves.…”
Section: Introductionmentioning
confidence: 99%